Evidence of colonization of man-made ecotopes by Triatoma dimidiata (Latreille, 1811) in Costa Rica - Zeledón, Rodrigo (2001)
Triatoma dimidiata adults have been frequently found, during the last five years, in a dog kennel and a chicken coop, in the back yard of a well-built house, 15 km from San José, the capital of Costa Rica. In the chicken coop nymphs were also found. Two of the 11 dogs from the kennel were serologically positive for Trypanosoma cruzi infection. The inhabitants of the house, three adults and two children, were negative. This type of colonization by the insect, which is attracted to lights, is becoming common in old and new settlements, with different degrees of success, a fact with epidemiological implications and great relevance in the control strategies that can be applied.